Diversity Management und diversitätsbasiertes Controlling: von der Diversity Scorecard zur Open Balanced Scorecard - Carsten Herrmann-Pillath (Frankfurt School of Finance & Management, 2009)
In recent years, diversity management has evolved from a perspective on human resources management toward a conception of strategic management. This implies the need to adapt a central management function, strategic controlling, in order to render the conception of diversity management in established categories of operative management. Starting out from the existing proposal of a diversity scorecard, this paper extends the DM approach into the notion of an open balanced scorecard. The open balanced scorecard results from the application of DM principles on this widely used management tool. The argument is based on an overview of existing approaches to DM and their critical evaluation.
urn:nbn:de:101:1-200907211341
Keywords: M12; M14; 330; Diversity management; cognitive diversity; balanced scorecard